Source codeVideos

Command Palette

Search for a command to run...

Function Composition and Inverse Function

Properties of Inverse Function

Property of Composition with Inverse

This property is the core of the inverse function definition: the inverse function "undoes" the effect of the original function, and vice versa. If we compose a function with its inverse (in any order), we get the identity function I(x)=xI(x) = x.

  1. Composition of ff with f1f^{-1}:

    (ff1)(x)=f(f1(x))=x(f \circ f^{-1})(x) = f(f^{-1}(x)) = x

    This holds for all xx in the domain of f1f^{-1} (which is the range of ff).

  2. Composition of f1f^{-1} with ff:

    (f1f)(x)=f1(f(x))=x(f^{-1} \circ f)(x) = f^{-1}(f(x)) = x

    This holds for all xx in the domain of ff.

Example:

We know that if f(x)=2x+3f(x) = 2x + 3, its inverse is f1(x)=x32f^{-1}(x) = \frac{x - 3}{2}. Let's verify the composition property:

  • f(f1(x))=f(x32)=2(x32)+3=(x3)+3=xf(f^{-1}(x)) = f\left(\frac{x - 3}{2}\right) = 2\left(\frac{x - 3}{2}\right) + 3 = (x - 3) + 3 = x
  • f1(f(x))=f1(2x+3)=(2x+3)32=2x2=xf^{-1}(f(x)) = f^{-1}(2x + 3) = \frac{(2x + 3) - 3}{2} = \frac{2x}{2} = x

Both compositions result in xx, as expected.

Property of the Inverse of an Inverse

If we find the inverse of an inverse function, we get back the original function.

(f1)1(x)=f(x)(f^{-1})^{-1}(x) = f(x)

This makes sense because the process of finding an inverse is a "reversal". If we reverse something twice, we return to the original state.

Property of the Inverse of a Composition

If we have a composition of two functions, both of which have inverses, the inverse of the composition is the composition of their inverses, but in reverse order.

Let ff and gg be two functions with inverses f1f^{-1} and g1g^{-1}. Then the inverse of the composition fgf \circ g is:

(fg)1(x)=(g1f1)(x)(f \circ g)^{-1}(x) = (g^{-1} \circ f^{-1})(x)

Note the reversed order: g1g^{-1} is applied first, then f1f^{-1}.

Analogy: Imagine putting on socks (gg) and then shoes (ff). To undo this (the inverse), you must take off the shoes (f1f^{-1}) first, then take off the socks (g1g^{-1}). The order is reversed.

Example:

Let f(x)=x+1f(x) = x + 1 (its inverse is f1(x)=x1f^{-1}(x) = x - 1) and g(x)=3xg(x) = 3x (its inverse is g1(x)=x3g^{-1}(x) = \frac{x}{3}).

  1. Find (fg)(x)(f \circ g)(x):

    (fg)(x)=f(g(x))=f(3x)=3x+1(f \circ g)(x) = f(g(x)) = f(3x) = 3x + 1
  2. Find the inverse of (fg)(x)(f \circ g)(x):

    Let y=3x+1y = 3x + 1. Swap xx and yy: x=3y+1x = 3y + 1.

    Solve for yy: x1=3y    y=x13x - 1 = 3y \implies y = \frac{x - 1}{3}.

    So, (fg)1(x)=x13(f \circ g)^{-1}(x) = \frac{x - 1}{3}.

  3. Find (g1f1)(x)(g^{-1} \circ f^{-1})(x):

    (g1f1)(x)=g1(f1(x))=g1(x1)(g^{-1} \circ f^{-1})(x) = g^{-1}(f^{-1}(x)) = g^{-1}(x - 1)
    g1(x1)=x13g^{-1}(x - 1) = \frac{x - 1}{3}

Since the results from steps 2 and 3 are the same, it is proven that (fg)1(x)=(g1f1)(x)(f \circ g)^{-1}(x) = (g^{-1} \circ f^{-1})(x).

Domain and Range Relationship

The domain of the original function ff becomes the range of its inverse function f1f^{-1}, and the range of the original function ff becomes the domain of its inverse function f1f^{-1}.

Domain(f)=Range(f1)\text{Domain}(f) = \text{Range}(f^{-1})
Range(f)=Domain(f1)\text{Range}(f) = \text{Domain}(f^{-1})